Fountain house : creating community in mental health practice - Doyle, Alan (Columbia University Press, 2013)
Since 1948, people suffering from mental health issues, mental health professionals, and committed volunteers have gathered at Fountain House in New York City to find relief from stigmatisation and social alienation. Its 'working community' approach has earned the organisation vast critical recognition, enabling it to replicate its methods across the world. This volume describes the humanity, social inclusivity, personal empowerment, and perpetual innovation of the Fountain House approach.